Continuous Monitoring of Tau-Induced Neurotoxicity in Patient-Derived iPSC-Neurons - Oakley, Derek H. (J Neurosci, 2021)
Tau aggregation within neurons is a critical feature of Alzheimer's disease (AD) and related tauopathies. It is believed that soluble pathologic tau species seed the formation of tau aggregates in a prion-like manner and propagate through connected neurons during the progression of disease. Both soluble and aggregated forms of tau are thought to have neurotoxic properties. In addition, different strains of misfolded tau may cause differential neurotoxicity. In this work, we present an accelerated human neuronal model of tau-induced neurotoxicity that incorporates both soluble tau species and tau aggregation. Using patient-derived induced pluripotent stem cell (iPSC) neurons expressing a tau aggregation biosensor, we develop a cell culture system that allows continuous assessment of both induced tau aggregation and neuronal viability at single-cell resolution for periods of >1 week. We show that exogenous tau “seed” uptake, as measured by tau repeat domain (TauRD) reporter aggregation, increases the risk for subsequent neuronal death in vitro. These results are the first to directly visualize neuronal TauRD aggregation and subsequent cell death in single human iPSC neurons. Specific morphologic strains or patterns of TauRD aggregation are then identified and associated with differing neurotoxicity. Furthermore, we demonstrate that familial AD iPSC neurons expressing the PSEN1 L435F mutation exhibit accelerated TauRD aggregation kinetics and a tau strain propagation bias when compared with control iPSC neurons. SIGNIFICANCE STATEMENT Neuronal intracellular aggregation of the microtubule binding protein tau occurs in Alzheimer's disease and related neurodegenerative tauopathies. Tau aggregates are believed to spread from neuron to neuron via prion-like misfolded tau seeds. Our work develops a human neuronal live-imaging system to visualize seeded tau aggregation and tau-induced neurotoxicity within single neurons. Using an aggregation-sensing tau reporter, we find that neuronal uptake and propagation of tau seeds reduces subsequent survival. In addition, human induced pluripotent stem cell (iPSC) neurons carrying an Alzheimer's disease-causing mutation in presenilin-1 undergo tau seeding more rapidly than control iPSC neurons. However, they do not show subsequent differences in neuronal survival. Finally, specific morphologies of tau aggregates are associated with increased neurotoxicity.